Portraying economic competence in Malaysian federal budget speeches - Kumaran Rajandran (Penerbit Universiti Kebangsaan Malaysia, 2019)
Budget speeches are a fixed political event in Malaysia. Their content involves the whole country and a variety of domains. Despite the cornucopia of research on speeches, budget speeches are rarely selected and speeches from Malaysia have not been examined in detail. The discourse in these speeches can display how a developing country tackles economic decision-making. The article explores the portrayal of economic competence in Malaysian federal budget speeches. It conducts a linguistic analysis grounded in critical discourse studies. The analysis employs frequency, concordance and the representation of social actors to decipher monetary amount, politonyms, ethnonyms and toponyms. The discourse in budget speeches can portray economic competence, which has three characteristics. First, the government can claim to be financially solvent and propose significant initiatives. Second, the government introduces desirable initiatives because it intervenes to ensure economic growth. Third, the government helps citizens of several ethnicities and regions although Bumiputeras, Sabah and Sarawak are prioritized. The portrayal entails an ideological government-citizen binary because the government is the source of initiatives while citizens are the target of initiatives. The portrayal was reproduced in other texts and was repeated in the media. The portrayal became the endorsed way to think about the former Barisan Nasional (BN) government but other parties questioned it. The article argues that BN sought to legitimize its political power but its legitimacy became compromised, and it was defeated in the 2018 general elections.